Intraspinal stimulation with a silicon-based 3D chronic microelectrode array for bladder voiding in cats. (16th December 2020) - Pikov, Victor; McCreery, Douglas B; Han, Martin
Abstract: Objective. Bladder dysfunction is a significant and largely unaddressed problem for people living with spinal cord injury (SCI). Intermittent catheterization does not provide volitional control of micturition and has numerous side effects. Targeted electrical microstimulation of the spinal cord has been previously explored for restoring such volitional control in the animal model of experimental SCI. Here, we continue the development of the intraspinal microstimulation array technology to evaluate its ability to provide more focused and reliable bladder control in the feline animal model. Approach. For the first time, a mechanically robust intraspinal multisite silicon array was built using novel microfabrication processes to provide custom-designed tip geometry and 3D electrode distribution. Long-term implantation was performed in eight spinally intact animals for a period up to 6 months, targeting the dorsal gray commissure area in the S2 sacral cord that is known to be involved in the coordination between the bladder detrusor and the external urethral sphincter. Main results. About one third of the electrode sites in the that area produced micturition-related responses. The effectiveness of stimulation was further evaluated in one of eight animals after spinal cord transection (SCT). We observed increased bladder responsiveness to stimulation starting at 1 month post-transection, possibly due to supraspinal disinhibition of the spinal circuitry and/or hypertrophy and hyperexcitability of the spinal bladder afferents. Significance . 3D intraspinal microstimulation arrays can be chronically implanted and provide a beneficial effect on the bladder voiding in the intact spinal cord and after SCT. However, further studies are required to assess longer-term reliability and safety of the developed intraspinal microstimulation array prior to eventual human translation.